Estimating the effects of race and social vulnerability on hospital admission and mortality from COVID-19. Issue 4 (22nd December 2021) - Landman, Joshua M; Steger-May, Karen; Joynt Maddox, Karen E; Hammond, Gmerice; Gupta, Aditi; Rauseo, Adriana M; Zhao, Min; Foraker, Randi E
Abstract: Objective: To estimate the risk of hospital admission and mortality from COVID-19 to patients and measure the association of race and area-level social vulnerability with those outcomes. Materials and Methods: Using patient records collected at a multisite hospital system from April 2020 to October 2020, the risk of hospital admission and the risk of mortality were estimated for patients who tested positive for COVID-19 and were admitted to the hospital for COVID-19, respectively, using generalized estimating equations while controlling for patient race, patient area-level social vulnerability, and time course of the pandemic. Results: Black individuals were 3.57 as likely (95% CI, 3.18–4.00) to be hospitalized than White people, and patients living in the most disadvantaged areas were 2.61 times as likely (95% CI, 2.26–3.02) to be hospitalized than those living in the least disadvantaged areas. While Black patients had lower raw mortality than White patients, mortality was similar after controlling for comorbidities and social vulnerability. Discussion: Our findings point to potent correlates of race and socioeconomic status, including resource distribution, employment, and shared living spaces, that may be associated with inequitable burden of disease across patients of different races. Conclusions: Public health and policy interventions should address these social factors when responding to the next pandemic. Lay Summary: Using records from a hospital system spanning multiple sites and 2 states, we examined patients' risk of hospital admission and death due to COVID-19 over the first 6 months of the pandemic. Specifically, we measured the association of race and social vulnerability with the likelihood of admission and death. Our statistical models showed that Black patients were 3.57 times more likely than White patients to be hospitalized. We also took into account how socially vulnerable a given US Census tract is, and when incorporating that into our models, we estimated that patients living in the most disadvantaged areas were 2.61 times as likely to be hospitalized as those living in the least disadvantaged areas. We found no difference in mortality by race when controlling for underlying conditions and social vulnerability. These findings suggest that public health and policy interventions should address such things as resource distribution, employment, and shared living spaces, and other social factors that may be associated with race, socioeconomic status, and the inequitable burden of disease across patients of different races.